Innovative Approach to the Development of Students on The Basis of the Spiritual Kompetensiya a Volleyball Game - Nosirova Dilnoza Sobirovna (Genius Publishing Group, 2022)
In this article, the essence of the development of spiritual competencies of students on the basis of an innovative approach volleyball game is comprehensively covered.
Keywords: technique; tactics; game skills; game discipline